ANALYSIS INFLUENCE STRESS WORK , WORKLOAD AND ENVIRONMENT WORK TO TURNOVER INTENTION EMPLOYEES AT THE BHAKTI SUCI EDUCATION FOUNDATION PURWODADI REGENCY GROBOGAN - Fidyah Yuli Ernawati; Arini Novandalina; Rokhmad Budiyono; Egiliana Atika Putri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
High employee turnover rate _ resulted organization Becomes no effective , lose employee experienced and necessary practice employee new . stress high work _ as well as environment good work _ will effect on the decline level turnover intention, meanwhile burden high work _ will effect on the increase turnover intention. Study this use study quantitative with survey method that takes sample from whole population and use questionnaire as well as Interview as tool collect key data with scale likert and processed using the IBM SPSS 25 program . Variables used in study this covers variable free stress work , load work and environment work whereas variable bound by turnover intention. Population in study this is Bhakti Suci Education Foundation employees Data obtained then conducted analysis includes : validity test, reliability test, assumption test composed classic _ from : normality test, multicollinearity test, heteroscedasticity test , analysis multiple linear regression , t test, F test, and analysis coefficient determination . Population in study this is whole employees of the Bhakti Suci Education Foundation Purwodadi Regency Grobogan , with sample as many as 60 respondents . Retrieval technique sample in research this is sample fed up or sample census , where all member population made sample . Research t test results this show that variable stress work (X1 ) effect in a manner Partial on turnover intention with score significant 0.742, variable burden work (X2) effect in a manner Partial or separated on employee turnover intention with score significant of 0.00. Environment variables work (X3) effect in a manner Partial or separated on employee turnover intention with score significant of 0.035. Advice for company should give addition incentive for employee , put employee in accordance with expertise , added employee cleanliness . For other researchers can add objects and variables other.